Dietary Forage Legume (Onobrychis altissima grossh.) Supplementation on Serum/Yolk Cholesterol, Triglycerides and Egg Shell Characteristics in Laying Hens - Rahimi, G. (International Journal of Poultry Science, 2005)
In recent years, the consumer`s desire for healthier foods has increased the demand for animal products containing low cholesterol and enriched with omega-3 fatty acids. In response to the perceived need, poultry researchers have focused on reducing egg yolk cholesterol to satisfy the health conscious of consumers. The present study was conducted to determine the effects of dietary forage legume supplementation on plasma triglyceride and cholesterol concentrations, egg yolk cholesterol contents and egg shell characteristics in indigenous laying hens at Mazandaran Native Fowls Breeding Station in north of Iran. A total of 60 laying hens were kept under commercial conditions from 35-45 weeks of age and were fed a commercial isocaloric and isonitrogenous corn-soybean meal diet. Birds were divided randomly into six treatment groups of ten birds each, and fed diets containing 0, 0.75, 1.25, 2.5, 5 and 10% added forage legume for 10 weeks. Ten eggs from each treatment groups were pooled in the last four-day of each period for the egg yolk cholesterol contents and egg shell breaking strength. The blood samples were taken from the wing-vein at the end of each period from all birds of each treatment groups for serum triglyceride and cholesterol contents. The results showed that there were no significant differences in final body weight, egg weight and yolk weight due to different forage legume treatments. Forage legume supplementation to the diet did not significantly affect plasma cholesterol and triglyceride concentration, while it has significantly (p